(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazione SOMMARIO: 1. Premessa – 2. La concezione della ricchezza nel mondo musulmano - 3. Il waqf all’interno del sistema dei “furu al figh”. Definizione di waqf o hubus - 4. IlBonyads, le fondazioni di beneficienza nella variante sciita – 5. La struttura del waqf khayrì - 6. Gli elementi costitutivi delle causae piae e del waqf khayrì a confronto - 7. Il negozio giuridico costitutivo delle causae piae e del waqf khayrì - 8. Caratteri strutturali comuni e analoga funzione dei due istituti giuridici: effetti rispetto ai beni che ne costituiscono l’oggetto - 9. Confronto tra i regimi giuridici relativi al subiectum administrationis nelle causae piae e nel waqf khayrì - 10. Alcune riflessioni conclusive. ABSTRACT The return of waqf The essay reconstruct role and structure of the waqf, typical institution of Islamic law, by a comparison of it with the “causae piae”, to highlight the concordances and differences, emphasizing the institution’s use in the management of the charity and of places of worship in the Muslim ambit, in particular mosques and activities related to them. Particular attention is paid to the activities with social purposes for the realization of the Islamic Welfare, operated by religious communities, with believers support (public waqf). Frequent are the references to the charity structure in the Anglo-Saxon law. The Autor envisages the opportunity to a number of agreements with the various components of Islam, in which specific parts can find a place, dedicated to waqf as entity inspired by religious reasons, and a review of the general favorable legislation ensured by the State to all religious bodies, and to those who carry out social activities obtaining profit.